Integration of Islamic Religious Education, Islamic Psychology, and Neuroscience in the Formation of Faith-Based Character - Wahidah Wahidah; Hamdan Hamdan; Syaifuddin Sabda; Husnul Yaqin (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study examines the integration of Islamic Religious Education (IRE), Islamic Psychology, and Neuroscience as a holistic approach to developing faith-based character. To date, character education has tended to emphasize cognitive and moral aspects while overlooking Islamic psychological dimensions and the biological foundations that influence human behavioral development. Through theoretical analysis, this study demonstrates that IRE plays a fundamental role in instilling the values of creed, worship, and ethics; Islamic Psychology provides a framework for understanding human psychological dynamics based on the concepts of fitrah, qalb, and nafs; while Neuroscience explains the neurobiological processes that contribute to habit formation, self-control, and the internalization of values. The integration of these three disciplines produces a more comprehensive character education model by combining spiritual foundations, psychological understanding, and the mechanisms of brain function. The findings highlight the importance of multidisciplinary collaboration in developing learning strategies that not only cultivate intellectual intelligence but also strengthen students’ faith, morality, and psychological well-being. These insights are expected to serve as a reference for educators in designing curricula and learning methods that are more effective and oriented toward holistic character formation.